The risk of developing colorectal cancer in individuals aged 50-70 years and behavioral changes in high-risk individuals regarding a fecal occult blood test - Öztürk Dönmez, Renginar; Özsoy, Süheyla; Ardahan, Melek (Journal of Surgery and Medicine, 2022)
Background/Aim: The prognosis of colorectal cancer (CRC) is highly associated with its stage; therefore, it is important to determine the risk factors. Risk determination tools such as CRC-PRO are patient-friendly since they are non-invasive, and highly successful in predicting the cancer risk. This study aimed to determine the risks of getting CRC in individuals aged 50-70 years and the early diagnosis behaviors of individuals, who were deemed at high risk based on a Fecal Occult Blood Test (FOBT). Methods: This single-group quasi-experimental follow-up study was conducted in a family health center in Turkey between December 2016-December 2017. The data were collected using the “CRC Predicted Risk Online (CRC-PRO)” and “stages of change form.” The patients were educated at the risk determination stage. Along with telephone counseling conducted with individuals in the first and sixth months, the changes in FOBT were noted. Results: The CRC-PRO mean risk scores of the males and females were 1.37 (0.74), and 0.79 (0.40), respectively. Among them, 33.5% of males and 25.8% of females had a risk of CRC. After they were educated for FOBT, their behaviors positively and significantly changed from the risk determination stage until the 6th-month follow-up. Conclusion: With the use of risk determination tools, individuals' lifestyle characteristics can be determined, and health education can be provided to change them.